Economic recession, parental unemployment and adolescents' health-related quality of life and mental health outcomes in Greece - Nick Drydakis (Global Labor Organization (GLO), 2022)
This study examines whether an association exists between parental unemployment and health-related quality of life and mental health for adolescents aged 15-18 in Athens, Greece. The gathered dataset covers the same upper high schools in two periods, 2011-2013 and 2017-2019. The study finds that parental unemployment bears an association with decreased health-related quality of life and increased adverse mental health symptoms for adolescents. Moreover, the 2011-2013 period, a period of increased parental unemployment, saw a decrease in health-related quality of life and increased adverse mental health symptoms for adolescents. In addition, parental unemployment proved more detrimental to adolescents' health-related quality of life and mental health in 2011-2013 than in 2017-2019. The present research ranks among the first studies to examine whether parental unemployment could be associated with worse health-related quality of life and mental health for adolescents during periods of increased parental unemployment. Public policies that can reduce the adverse effects of parental unemployment on adolescents' health-related outcomes require consideration. This approach proves critical because deteriorated health-related quality of life and mental health can negatively impact on adolescents' human capital, progression, income, and future health.
Keywords: E24; J13; I10; I14; 330; Parental unemployment; adolescents; health-related quality of life; mental health; recession; economic crisis